A Study on Employee Retention Strategies with Reference to IT Industry - V.Suneel Kumar; Dr.P.Raghunadha Reddy (Educational Administration: Theory and Practice, 2023)
In a company, employee retention is crucial since it has an impact on productivity. The goal of this study is to determine how various employee retention tactics, such as performance-based bonuses, flexible work schedules, timely promotions, and career development programmes, affect both employee performance and retention. The study’s findings indicated that employee retention techniques had a favourable impact on both employee performance and retention. As employees are expensive to acquire and difficult to retain, the theoretical framework of this study would encourage businesses and their employers to consider them vital resources. Researchers and academics could also benefit from the study’s understanding of the significance of staff retention in a firm. This study’s main goal is to identify and examine the key determinants that influence employee retention. The following broad factors were examined in-depth in this study: health and wellness benefits, personal growth, compensation, work-life balance, recognition and rewards for top performers, superior-subordinate relationships, training and development, job characteristics and job commitment, monetary rewards, and welfare programmes. Data from 615 self-administrative questionnaires were collected, and SPSS v20 software was used to analyse the data. The findings showed that effective staff retention methods are crucial to both high levels of employee satisfaction and business performance. The study’s findings will help businesses understand the importance of employee retention elements and methods in achieving superior organisational overall performance and retaining qualified personnel.